Paleoclimatic record from the clay mineralogy of Quaternary sediments of drill core DWJ from Jiudong subbasin (western Hexi Corridor), NW China. Issue 1 (January 2020) - Chen, Dianbao; Pan, Baotian; Ma, Jinfeng; Hu, Xiaofei; Geng, Haopeng; Pang, Hongli
Abstract: The thick sedimentary deposits of the Jiudong subbasin in the western Hexi Corridor of NW China can potentially provide important records of climate change in arid and semiarid areas subject to the interaction of the East Asian summer monsoon (EASM) and the westerlies. Here we present the results of a study of the clay mineralogy of the sediments of drill core DWJ from the Jiudong subbasin. The clay minerals consist mainly of illite, followed by chlorite, kaolinite, and smectite. The clay mineral assemblages are used to define four paleoclimatic stages since 1.8 Ma: (1) During 1.8–1.2 Ma, the climate was relatively cold and arid; (2) during 1.2–0.9 Ma, it was relatively warm and wet, with strongly seasonal precipitation; (3) during 0.9–0.3 Ma, there was a long-term trend of cooling and drying; and (4) during 0.3–0.1 Ma, the climate was warmer and wetter than during the previous period, with strongly seasonal precipitation. The paleoclimatic record of the Jiudong subbasin since 1.8 Ma is consistent with records from the Tengger Desert and typical monsoonal areas. This suggests that the EASM penetrated into the central regions of the North Qilian Shan and Zhangye–Jiudong subbasin during 1.2–0.9 and 0.3–0.1 Ma.